Evaluating The Impact of Data-Driven Decision Making on Market and Financial Performance in Healthcare Companies - Jeet, Vikram; Ali, Nasir; Qazi, SayeeduzZafar; Nazneen, Afroze; Allam, Zafrul (Journal of Cultural Analysis and Social Change, 2025)
The study investigates the role of business analytics in enhancing organizational performance within healthcare companies. The study highlights the elements of business analytics such as data collection & management, analytical tools & techniques, technology & infrastructure, and compliance & ethics are crucial for driving informed decision-making and strategic planning. A quantitative approach was employed, surveying 162 professionals across various managerial levels in healthcare companies. A structured questionnaire was designed to measure the use of business analytics tools and techniques, and their perceived impact on organizational performance across different dimensions such as financial performance and market performance. The data was analyzed using SPSS and Smart PLS 4 software. To address the study’s objective, regression analysis is performed to examine the relationship between the use of business analytics and various organizational performance metrics. The study concluded that data collection and management are the cornerstones of financial and market performance in the healthcare sector, with compliance and ethics. Analytical tools and techniques also provide a meaningful supplementary contribution. The results support the importance of data integration approaches as a basis for the long-term profitability and success of healthcare companies in the market. Though compliance and ethics are also essential for stability in regulation and investor confidence, they do comparatively little to influence competitive positioning within the market. The findings underscore the critical role of business analytics in improving financial performance and market performance. This study provides empirical evidence of the significant impact of business analytics on organizational performance in the healthcare sector, highlighting its potential to transform decision-making processes and strategic planning.